Dynamics of Ragweed Pollen Concentration in the Air of Ivano-Frankivsk - Halyna Melnychenko; Viktoriia Hrushka; Оlha Ivanova (Vasyl Stefanyk Precarpathian National University, 2022)
The article updates the conduct of aeropalynological monitoring in Ukraine because today, there are only a few studies in the country that cannot be automatically extrapolated to other regions, as the diversity of climatic zones affects the duration of pollination and pollen grains in the air. Furthermore, this type of research is needed due to the increasing number of people suffering from pollen allergies (hay fever). The research was conducted in the city of Ivano-Frankivsk (western Ukraine) from early February to mid-October 2019, using a gravimetric Durham pollen collector installed on the roof of the Faculty of Natural Sciences of Vasyl Stefanyk Precarpathian National University (24 m from the ground). The pollen grains were counted using an Olympus CX-300 light microscope (magnification x 400). The main goal was to study the aeropalynological spectrum of the city and the dynamics of concentrations of ragweed pollen grains (the most important plant allergen). The study determined the aeropalynological spectrum of Ivano-Frankivsk and provided data on pollination of the following taxa: Betula, Quercus, Acer, Fraxinus, Pinus, Juglans, Carpinus, Alnus, Populus, Urticaceae, Poaceae, Artemisia, and Ambrosia; conducted a comparative characterization with the spectra of the cities of Vinnytsia (central Ukraine) and Zaporizhia (southern Ukraine); determined the beginning and end of pollination of ragweed and the peak of its flowering, as well as conducted a comparative description with last year's data. Seeing an alarming trend, there is a need to continue to conduct aeropalynological monitoring to create calendars of sawing and alleviate the course of allergies in people prone to it.